Triple Dirichlet average and fractional Derivative - Deora, Yogendra; Banerji, P. (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
The object of the present paper is to establish some results of triple Dirichlet average, using fractional calculus.